Representasi Nilai Budaya Sastra Pedalangan Wayang Golek: Analisis Wacana Kritis Model Fairclough - Jaelani, Alan; Solo, Lenny (Program Studi Magister Linguistik Terapan UNJ, 2024)
Revitalization in Article 26 paragraph (3) of Law Number 5 of 2017 supports the preservation and strengthening of local cultural values through traditional arts. This study aims to reveal the representation of cultural values in traditional wayang golek performances using a critical discourse analysis approach based on Norman Fairclough's model. This study employs qualitative research in the form of critical discourse analysis. The analysis focuses on four discourse elements found in the literary aspects of wayang golek puppetry: murwa, nyandra, antawacana, and tembang. Each discourse element is elaborated through Fairclough's three dimensions of analysis: text, discourse practice, and socio-cultural practice. The results show that murwa conveys religious and moral messages, reminding the audience of the importance of their relationship with God and nature. Nyandra illustrates wisdom in facing life and challenges, while antawacana voices criticism of social and political injustices, emphasizing the importance of honesty in governance. Tembang, sung by the sinden, reinforces moral and spiritual messages, encouraging the audience to maintain harmony in life. This study provides insights into the significance of wayang golek performances as a medium for teaching cultural values and moral lessons within Sundanese society.